CHILDHOOD OBESITY AND PREVENTION - Sabani, Havva; Saban, Yasemin (International Scientific Journal Vision, 2022)
The World Health Organization (WHO) defines childhood obesity as one of the most serious public health problems of the 21st century. In its simplest definition, obesity is an increase in excessive fat accumulation in the body in a way that impairs health. If the energy taken with food is more than the energy spent, the excess energy is stored as fat in the body and causes obesity. Obesity has negative effects on all systems and psychological states in the body, and these effects cause many health problems. Childhood obesity is a serious medical condition that affects children and adolescents. Being healthy is not limited to the physical well-being of the child. At the same time, the child’s psychological well-being is a condition that creates a whole with the development of a positive self-perception about himself. Preventing obesity is crucial to the health and well-being of children. Prevention of obesity in children can achieve with parents’ conscious and active participation. In this study, childhood obesity and its precautions were compiled by researching various publications.